Raising Awareness and Creating a Safer School Environment Through Understanding Tween Bullying - Tygo Van Hasselt; Ni Putu Indah Cahya Prihatina (Global Education Journal, 2026)
Bullying among tweens remains a significant educational and social concern because it affects emotional well-being, peer relationships, and academic engagement during a critical stage of child development. This study examines why bullying occurs among tweens and how safer school environments can be created by interpreting bullying through Michel Foucault’s concept of power. The research uses an exploratory descriptive design that combines Socratic questioning, literature review, and a small classroom survey involving eight students. The analysis shows that participants most frequently associated bullying with physical and cyber forms, while jealousy, insecurity, stress, social conflict, and the perception that bullying is enjoyable emerged as recurring explanations for why students bully others. Interpreted through a Foucauldian lens, these findings suggest that bullying is not only an individual behavioral problem but also a relational and institutional issue shaped by unequal power, peer hierarchies, and limited opportunities for students to exercise voice. The study argues that prevention requires more than punishment. Schools need to strengthen supervision, cultivate fairness and empathy, decentralize opportunities for student participation, and create supportive structures that reduce the rewards of domination. The article contributes to bullying scholarship by showing how a Foucauldian perspective can deepen understanding of tween bullying while remaining closely connected to practical school-based prevention.